ANALYSIS OF FACTORS AFFECTING TAX AVOIDANCE ON AGRICULTURAL COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2020 – 2023 - Vera Mardiana; Achmad Fadjar (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This consider investigates how productivity, use, and firm estimate affect tax evasion in agricultural firms on the Indonesia Stock Trade from 2020 to 2023 are the think about population. Only 26 companies met the sampling criteria, therefore 104 available data were taken as samples The study employs purposive sampling, with secondary data analyzed through multiple regression methods to investigate how each variable affects tax avoidance and are processed using IBM SPSS Statistics 27 software. The data used are sourced from annual financial reports officially published through the website www.idx.co.id. The investigation comes about show that profitability (ROA) essentially impacts charge shirking, whereas use (DER) does not have a critical affect. Also, company estimate is appeared to essentially influence tax avoidance. Collectively, productivity, use, and company measure have a concurrent impact on tax avoidance.